2020
DOI: 10.3390/ijms21176116
|View full text |Cite
|
Sign up to set email alerts
|

Global Quantitative Proteomics Studies Revealed Tissue-Preferential Expression and Phosphorylation of Regulatory Proteins in Arabidopsis

Abstract: Organogenesis in plants occurs across all stages of the life cycle. Although previous studies have identified many genes as important for either vegetative or reproductive development at the RNA level, global information on translational and post-translational levels remains limited. In this study, six Arabidopsis stages/organs were analyzed using quantitative proteomics and phosphoproteomics, identifying 2187 non-redundant proteins and evidence for 1194 phosphoproteins. Compared to the expression observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 94 publications
1
6
1
Order By: Relevance
“…To provide insight into the possible cellular mechanisms, comprehensive protein-protein interactions (PPIs) were used to depict numerous biological aspects of complex regulatory networks and signaling pathways. Hence, we used a multi-omics data analysis tool, OmicsBean, to construct PPI networks (Huang et al 2020;Lu et al 2020b;Szklarczyk et al 2016) for DEPs. Before the induced differentiation stage, we found that the PPIs from Msx1-mediated differentiation might play important roles in amino sugar and nucleotide sugar metabolism, arginine and proline metabolism, glycolysis/gluconeogenesis (Fig.…”
Section: Ppis Network Of Deps Involved In Msx1and Msx2-mediated Myobl...mentioning
confidence: 99%
See 4 more Smart Citations
“…To provide insight into the possible cellular mechanisms, comprehensive protein-protein interactions (PPIs) were used to depict numerous biological aspects of complex regulatory networks and signaling pathways. Hence, we used a multi-omics data analysis tool, OmicsBean, to construct PPI networks (Huang et al 2020;Lu et al 2020b;Szklarczyk et al 2016) for DEPs. Before the induced differentiation stage, we found that the PPIs from Msx1-mediated differentiation might play important roles in amino sugar and nucleotide sugar metabolism, arginine and proline metabolism, glycolysis/gluconeogenesis (Fig.…”
Section: Ppis Network Of Deps Involved In Msx1and Msx2-mediated Myobl...mentioning
confidence: 99%
“…Peptide Preparation was performed previously (Lu et al 2020a). Briefly, after sonicating the cells with lysis buffer.…”
Section: Peptide Preparation and Itraq Reagent Labelingmentioning
confidence: 99%
See 3 more Smart Citations